Расчет статической деформации сильфона вакуумных выключателей среднего напряжения - Байда, Е.И. (Електротехніка і електромеханіка, 2011)
The article deals with FEM determination of vacuum circuitbreaker bellows static deformation under influence of atmospheric pressure as function of the contacts travel. Dependences of the material stress on the bellows wall thickness for a given contacts travel are obtained.